EFFICIENCY ANALYSIS OF TRADITIONAL TEA FARMS IN IRAN - Ghaderi, Z.; Menhaj, M. H.; Kavoosi-Kalashami, M.; Sanjari, S. M. (Economics of Agriculture, 2019)
This study aimed at analyzing technical, allocative and economic efficiency of tea farms in Fouman County of Guilan Province, Northern Iran. Data were collected through questionnaire and face-to-face interviews with 200 tea farmers in 2017. The data then were analyzed using descriptive statistics, data envelopment analysis (DEA), as well as correlation analysis. The average technical, allocative and economic efficiency, assuming constant return to scale in input-oriented model, were found to be 86, 71 and 61 percent respectively. These figures for variable return to scale were 87, 74 and 65 percent respectively. These results indicate that over 60 percent of the surveyed farms enjoyed scale efficiency. Of those socio characteristics affecting tea farmers efficiency: age, educational level and family size had positive and significant correlation with technical efficiency. The findings suggest that, the elderly and better educated farmers combined their previous knowledge of farming adopting proper farming practices may achieve production efficiency.